Studi Laporan Kasus Reaksi yang Merugikan Pasca Vaksinasi Covid-19: Narrative Review - Ainina Al Shadrina; Kusnandar Anggadiredja (School of Pharmacy Institut Teknologi Bandung, 2022)
The accelerated Covid-19 vaccines’ emergency use authorization raises many questions regarding the safety and effectiveness of the vaccine due to the short duration of the pre-marketing clinical trial phase. In terms of vaccine safety, longer studies are needed, especially to see if there are long-term effects or unusual effects that were not detected during pre-marketing clinical trials. This study aims to summarize and assess the adverse reactions that occur after the administration of the Covid-19 vaccine that has obtained approval for emergency use. The search for case reports was carried out in the PubMed database with the keyword